Heterostructures of Cu2−xS/Cu2−xTe plasmonic semiconductors: disappearing and reappearing LSPR with anion exchange. Issue 70 (16th August 2022) - Espinosa, Alba Roselia; Novak, Marc; Luo, Qi; Hole, Brandon; Doligon, Clarisse; Prenza Sosa, Kenya; Gray, Jennifer L.; Rossi, Daniel P.; Plass, Katherine E.
Abstract : Converting Cu2− x S nanorods to Cu2− x Te through anion exchange resulted in unexpected effects on the LSPR behaviour. Abstract : Localized surface plasmon resonance (LSPR) of Cu2− x S nanorods is quenched during the initial Cu2− x S/Cu2− x Te core/shell stage of anion exchange then returns as Cu2− x Te progresses into the nanorod. Phase change within the core accounts for this behaviour illustrating the complexity emergent from anion exchange.